Revista Geográfica de América Central: 50 years contributing to academic exchange - Quirós Arias, Lilliam (2024)
The inaugural issue of the Revista Geográfica de América Central was published in 1974, featuring an emblematic statement for the geographical discipline: What is Geography today? This reflection explored the opportunities the discipline offered for those who wished to pursue it professionally. This question remains relevant 50 years after its inception, with the publication of its 73rd issue, volume 3. This article aims to review the journal’s trajectory over its 50 years of existence. Methodologically, the primary source utilized is the publications produced during this period, categorized by thematic areas. Since its foundation, the Revista Geográfica de América Central has facilitated academic exchange at a time when information was a scarce commodity. Throughout its history, the journal has adapted to scientific publication trends, adopting an open-access format to democratize information. It has achieved indexing in Latindex, Redalyc, and Scielo, as well as in various databases, directories, libraries, portals, repositories, and academic and social networks, thereby contributing to the internationalization of the knowledge generated through the journal.